Prototype Model for Final Project Evaluation and Student Satisfaction (Study at the AMIK Indonesia Banda Aceh Laboratory) - Sufyan Sufyan; Taufiq Iqbal (UNIVERSITAS SERAMBI MEKKAH, 2021)
The purpose of this study was to evaluate a student's final project using the prototype model for evaluation of student's final project at AMIK Indonesia Banda Aceh. The method used is a quantitative approach in order to analyze the level of success of the Prototype Model to evaluate students' final assignments. Data collection for user needs is carried out using data analysis techniques through observation, interviews and also literature studies to collect data used in the evaluation of students' final assignments. the prototype model of student final project evaluation at AMIK Indonesia Banda Aceh was measured using end user satisfaction (EUCS). The sample and function testing in this application is done by black box testing, all of which will work fine. The results of the prototype model of student final project evaluation at AMIK Indonesia Banda Aceh are correct based on the evaluation using the Boehm Turner radar chart. The success rate of the application of the Student Final Project Prototype Model at AMIK Indonesia Banda Aceh using the end user satisfaction (EUCS) at the level of satisfaction so that it can be concluded that the application of the student final project evaluation prototype model at AMIK Indonesia Banda Aceh is very appropriate to be developed.